DEVELOPMENT OF DESIGN STRENGTH PROGRAM FOR STEEL PROFILES USING THE NEW TURKISH STEEL CODE - Aydin, Levent; Alemdar, Fatih (YILDIZ TECHNICAL UNIV, 2017)
In this study, a computer program was developed to calculate the strengths of steel profiles according to the new Turkish Steel Structures Design and Construction Regulations (TSSDCR) to be utilized in steel structures lessons. This program is named as LETA Steel Strength and Visual Basic is used as programming language. All the effects specified in the regulations can be calculated within the program. The profile and material properties are determined by the selection menus, and the user cannot interfere with these standard features. This is especially intended to prevent calculation errors in prolonged process. Interfaces are designed on the basis of ease. The program is also suitable for engineering offices to use.
Keywords: Steel profile strength calculation; steel structure design; educational software; Engineering